Snake venom gene expression is coordinated by novel regulatory architecture and the integration of multiple co-opted vertebrate pathways - Perry, Blair W.; Gopalan, Siddharth S.; Pasquesi, Giulia I.M.; Schield, Drew R.; Westfall, Aundrea K.; Smith, Cara F.; Koludarov, Ivan; Chippindale, Paul T.; Pellegrino, Mark W.; Chuong, Edward B.; Mackessy, Stephen P.; Castoe, Todd A. (Genome Research, 2022)
Understanding how regulatory mechanisms evolve is critical for understanding the processes that give rise to novel phenotypes. Snake venom systems represent a valuable and tractable model for testing hypotheses related to the evolution of novel regulatory networks, yet the regulatory mechanisms underlying venom production remain poorly understood. Here, we use functional genomics approaches to investigate venom regulatory architecture in the prairie rattlesnake and identify cis-regulatory sequences (enhancers and promoters), trans-regulatory transcription factors, and integrated signaling cascades involved in the regulation of snake venom genes. We find evidence that two conserved vertebrate pathways, the extracellular signal-regulated kinase and unfolded protein response pathways, were co-opted to regulate snake venom. In one large venom gene family (snake venom serine proteases), this co-option was likely facilitated by the activity of transposable elements. Patterns of snake venom gene enhancer conservation, in some cases spanning 50 million yr of lineage divergence, highlight early origins and subsequent lineage-specific adaptations that have accompanied the evolution of venom regulatory architecture. We also identify features of chromatin structure involved in venom regulation, including topologically associated domains and CTCF loops that underscore the potential importance of novel chromatin structure to coevolve when duplicated genes evolve new regulatory control. Our findings provide a model for understanding how novel regulatory systems may evolve through a combination of genomic processes, including tandem duplication of genes and regulatory sequences, cis-regulatory sequence seeding by transposable elements, and diverse transcriptional regulatory proteins controlled by a co-opted regulatory cascade.
10.1101/gr.276251.121